A Survey of the Evolution of the Futuwwa (Knight-errant, Chivalry) Doctrine in Iran from the 3-8 A.H. / 8-14 A.D. Century - Karamipour, Hamid (Journal of History Culture and Art Research, 2018)
In the history of Iran, the doctrine of manliness and chivalry can be studied from many aspects due to its various socio-political functions from the ancient history to the present. Given their situation and requirements, different people and groups take benefit from the doctrines and mottos of manliness to present a humane and religious view of their craft. Moreover, different socio-political conditions have given rise to particular manifestations of manliness; sometimes manliness has taken an errantry aspect while some other times its religious and Sufi aspect is more highlighted. The current study, using an analytical-descriptive method, aims to present different aspects of manliness from the 3-8 AH / 8-14 AD century and show the revolutionary process of this doctrine.